Exploring Students' Learning Commitment Strata and Their Impact on Learning Outcomes - Zuvyati Aryani Tlonaen; Festif Rudolf Hoinbala; Zet Ena; Rohmatul Fitriyah Dewi (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
The problem addressed in this research is the variation in students' levels of learning commitment and how these differences impact their learning outcomes in a micro-teaching course. The samples were nine fifth-semester students (1 male and 8 females) from a Micro-teaching class, the English Language Education Study Program determined using purposive sampling with varying learning outcomes. Learning outcome data was taken from the final grades of the micro-teaching course. The learning commitment indicators consist of seven indicators arranged in 14 questions for each interview: interest in alternatives, acquiescence, cooperation, enhancement, identity, advocacy, and ownership. Data were analyzed using data reduction, data presentation, and conclusion. One student exhibited interest in alternatives commitment (score: 50.2), one student demonstrated acquiescence commitment (score: 61.1), three students showed advocacy commitment (scores: 75.5, 83.75, 89.75), and four students displayed ownership commitment (scores: 89.75, 90.6, 92.95, 95). No students were identified with cooperation, enhancement, or identity commitment strata. These results suggest a clear difference between students' learning commitment levels and learning outcomes in the microteaching course. The study concludes that students' learning commitment strata significantly impact learning outcomes, highlighting the importance of fostering strong learning commitment among students. The study recommends that educators implement strategies to strengthen students' learning commitment by encouraging higher levels of engagement and responsibility.